A Highly Sensitive NiO Flexible Temperature Sensor Prepared by Low-Temperature Sintering Electrohydrodynamic Direct Writing - Ting Wang; Xianruo Du; Gaofeng Zheng; Zhiyuan Xue; Junlin Zhang; Huatan Chen; Libo Gao; Wenwang Li; Xiang Wang; Yifang Liu; Jiaxin Jiang (Micromachines)
Flexible temperature sensors have diverse applications and a great potential in the field of temperature monitoring, including healthcare, smart homes and the automotive industry. However, the current flexible temperature sensor preparation generally suffers from process complexity, which limits its development and application. In this paper, a nickel oxide (NiO) flexible temperature sensor based on a low-temperature sintering technology is introduced. The prepared NiO flexible temperature sensor has a high-resolution temperature measurement performance and good stability, including temperature detection over a wide temperature range of (25 to 70 °C) and a high sensitivity performance (of a maximum TCR of −5.194%°C−1 and a thermal constant of 3938 K). The rapid response time of this temperature sensor was measured to be 2 s at 27–50 °C, which ensures the accuracy and reliability of the measurement. The NiO flexible temperature sensor prepared by electrohydrodynamic direct writing has a stable performance and good flexibility in complex environments. The temperature sensor can be used to monitor the temperature status of the equipment and prevent failure or damage caused by overheating.